Fine-tuned local coordination environment of Pt single atoms on ceria controls catalytic reactivity - Wei Tan; Shaohua Xie; Duy Le; Weijian Diao; Meiyu Wang; Ke-Bin Low; Dave Austin; Sampyo Hong; Fei Gao; Lin Dong; Lu Ma; Steven N. Ehrlich; et al. (Nature Communications, 2022)
CeO2-supported Pt single atoms with different coordination environments exhibit distinct behaviors in reactant adsorption/activation and product desorption, thus showing different catalytic performance for various catalytic oxidation reactions.